Oil Price Shocks : Can they Account for the Stagflation in the 1970's? - Hunt, Benjamin (IMF Working Papers; Working Paper, 2005)
Using a variant of the IMF's Global Economy Model (GEM), featuring energy as both an intermediate input into production and a final consumption good, this paper examines the macroeconomic implications of large increases in the price of energy. Within a fully optimizing framework with nominal and real rigidities arising from costly adjustment, large increases in energy prices can generate an inflation response similar to that seen in the 1970s if the monetary authority misperceives the economy's supply capacity and workers resist the erosion in their real consumption wages resulting from the price increase. In the absence of either of these two responses, the model suggests that energy price shocks cannot generate the type of stagflation witnessed in the 1970s. Further, even allowing for these two effects, the results do not suggest that the increase in the price of oil in late 1973 and early 1974 can fully explain the extent of the slowing in real activity or the magnitude of the acceleration in inflation experienced in the United States in 1974 and 1975.